Manajemen Masjid dalam Meningkatkan Partisipasi Remaja Milenial untuk Memakmurkan Masjid - Nudin, Ahmad Iman; Fakhruroji, Moch (Tadbir: Jurnal Manajemen Dakwah, 2023)
Millennial teenagers are currently able to improve the supervision process in an organization which has the ability to attract attention, one of which is the Al-Ikhlas mosque. This writing aims to determine the application of management functions at Al-Ikhlas Mosque in increasing Millennial Youth Participation to prosper the mosque through the POAC concept. The research method used is descriptive qualitative method. The results of this study indicate that the Al-Ikhlas Mosque in increasing the participation of millennial youth has a planning process in the form of preparing objectives, policy elements, progress elements, and program elements. The results of the study indicate that there is management in increasing the participation of millennial youth. mosque management in improving the function of the mosque provides skills to support various ongoing da’wah movements in the community to improve the function of the mosque. The application of functions and management elements made by IRMA in increasing the participation of millennial youth is able to increase the participation of millennial adolescents towards millennial adolescents in the mosque so that the function of the mosque can be optimized. The process carried out is able to carry out the management function of the Al-Ikhlas mosque.